Mapeamento do processo mecanizado de soldagem unilateral FCAW com backing cerâmico aplicável no passe de raiz em aço carbono - Silvio Trivellato Andrade (2007)
This work aims to evaluate one-sided welding automatic using the flux cored arc welding process with ceramic backing in the root bead. The tests were performed using a KUKA KR-16, robot for welding in the flat position. The wire is the AWS A5.20-79 E 71T-1, with 1.2 mm diameter, V-groove butt joints were design to be used in steel plate ASTM A-36. The process variables analyzed were Current, voltage, travel speed, root opening, groove geometry included angle and electrode inclination. It heat input was considered essential. It is the energy supplied for thecomposition of the parameters current, tension and speed, associated to the involved materials, steel carbon and backing ceramic and therefore responsible directly for the formation of the weld pool. The dimensional analysis considered height and width of the root reinforcement. The arc stability associated with the geometry of root reinforcement, visual quality of the bead, and macrographs were analyzed as the response for the ceramic weld backing. Twelve curves were elaborated, showing the relation of height and width root reinforcement with the parameters variation of Current, root opening, groove geometry included angle andelectrode inclination. The results allowed to establishing the best adjustment of the variables for root bead welding in flat position, that were current 205A, voltage 26V, travel speed 20cm/min, root opening 3 e 5mm, V-groove angle 40o e 60o and electrode inclination 15o, using ceramic backing with FCAW.